Synthesis of polydimethylsiloxane-block-polystyrene-block-polydimethylsiloxane via polysiloxane-based macroinitiator in supercritical CO2 - Akgün, M; Deniz, S; Baran, N; Uzun, NI; Akgün, NA; Dinçer, S (WILEY, 2005)
Polydimethylsiloxane-block-polystyrene-block-polydimethylsiloxane (PDMS-b-PS-b-PDMS) was synthesized by the radical polymerization of styrene using a polydimethylsiloxane-based macroazoinitiator (PDMS MAI) in supercritical CO2. PDMS MAI was synthesized by reacting hydroxy-terminated PDMS and 4,4'-azobis(4-cyanopentanoyl chloride) (ACPC) having a thermodegradable azo-linkage at room temperature. The polymerization of styrene initiated by PDMS MAI was investigated in a batch system using supercritical CO2 as the reaction medium. PDMS MAI was found to behave as a polyazoinitiator for radical block copolymerization of styrene, but not as a surfactant. The response surface methodology was used to design the experiments. The parameters used were pressure, temperature, PDMS MAI concentration and reaction time. These parameters were investigated at three levels (-1, 0 and 1). The dependent variable was taken as the polymerization yield of styrene. PDMS MAI and PDMS-b-PS-b-PDMS copolymers obtained were characterized by proton nuclear magnetic resonance and infrared spectroscopy. The number- and weight-average molecular weights of block copolymers were determined by gel permeation chromatography. (C) 2004 Society of Chemical Industry.
Keywords: polydimethylsiloxane-based macroazoinitiator; polydimethylsiloxane-block-polystyrene-block-polydimethylsiloxane; styrene; supercritical CO2; SILOXANE-BASED MACROMONOMER; CARBON-DIOXIDE; DISPERSION POLYMERIZATION; AZOBISCYANOPENTANOIC ACID; METHYL-METHACRYLATE; GLYCIDYL METHACRYLATE; COPOLYMERS; PARTICLES; SIZE; Polymer Science